The role of human endogenous retroviruses in gliomas: from etiological perspectives and therapeutic implications. Issue 10 (12th June 2021) - Shah, Ashish H; Gilbert, Mark; Ivan, Michael E; Komotar, Ricardo J; Heiss, John; Nath, Avindra
Abstract: Accounting for approximately 8% of the human genome, human endogenous retroviruses (HERVs) have been implicated in a variety of cancers including gliomas. In normal cells, tight epigenetic regulation of HERVs prevent aberrant expression; however, in cancer cells, HERVs expression remains pervasive, suggesting a role of HERVs in oncogenic transformation. HERVs may contribute to oncogenesis in several ways including insertional mutagenesis, chromosomal rearrangements, proto-oncogene formation, and maintenance of stemness. On the other hand, recent data has suggested that reversing epigenetic silencing of HERVs may induce robust anti-tumor immune responses, suggesting HERVs' potential therapeutic utility in gliomas. By reversing epigenetic modifications that silence HERVs, DNA methyltransferase, and histone deacetylase inhibitors may stimulate a viral-mimicry cascade via HERV-derived dsRNA formation that induces interferon-mediated apoptosis. Leveraging this anti-tumor autoimmune response may be a unique avenue to target certain subsets of epigenetically-dysregulated gliomas. Nevertheless, the role of HERVs in gliomas as either arbitrators of oncogenesis or forerunners of the innate anti-tumor immune response remains unclear. Here, we review the role of HERVs in gliomas, their potential dichotomous function in propagating oncogenesis and stimulating the anti-tumor immune response, and identify future directions for research.